Experiences with Ex Corde Ecclesiae in Faculty Teaching Practices at Southern Catholic Colleges - Maria Sarmiento; Pietro Sasso (Georgia Journal of College Student Affairs, 2021)
As special-mission institutions, Catholic higher education institutions pursue similar goals of American higher education to develop graduates who are civically engaged and ready to address contemporary challenges. However, these institutions are often challenged to integrate their religious mission within the classroom through faculty pedagogy, which buttresses academic freedom and student consumerism issues. This descriptive phenomenological study explored the lived experiences of Catholic university faculty members as they described their pedagogical experiences and Catholic identity perspectives. Findings from this study suggested a connection with Catholic identity, but that their relationship with institutional mission related to teaching was ambiguous. Participants had little professional development and called for their institutional leaders to better help them integrate Catholic mission and identity into their teaching approaches. Implications for practice include new ways of thinking to better support faculty teaching connection to institutional Catholic mission and identity.